2018
DOI: 10.1111/1744-7917.12564
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of C‐type lectin domain proteins in the ghost moth, Thitarodes xiaojinensis (Lepidoptera: Hepialidae)

Abstract: Insects have a large family of C-type lectins involved in cell adhesion, pathogen recognition and activation of immune responses. In this study, 32 transcripts encoding C-type lectin domain proteins (CTLDPs) were identified from the Thitarodes xiaojinensis transcriptome. According to their domain structures, six CTLDPs with one carbohydrate-recognition domain (CRD) were classified into the CTL-S subfamily. The other 23 CTLDPs with two CRDs were grouped into the immulectin (IML) subfamily. The remaining three w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Our phylogenetic analysis indicated that AgCTLGA , DmCG4115 and TcCTL6 formed one orthologous group. BmCTLS2 and BmCTLS3 were located closely in other sister subbranches (Meng et al , ). Moreover, amino acid sequence alignment analysis found that the orthologues possessed high sequence similarity and many common structural features, suggesting that they have similar functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our phylogenetic analysis indicated that AgCTLGA , DmCG4115 and TcCTL6 formed one orthologous group. BmCTLS2 and BmCTLS3 were located closely in other sister subbranches (Meng et al , ). Moreover, amino acid sequence alignment analysis found that the orthologues possessed high sequence similarity and many common structural features, suggesting that they have similar functions.…”
Section: Discussionmentioning
confidence: 99%
“…One of the five branches has three sister subbranches. The characteristics of two sister subbranches represented by BmCTLS2 and BmCTLS3 have been studied, whereas the functions of the other branch where TcCTL6 is located have not been studied (Meng et al , ). In this study, TcCTL6 was cloned for the first time from T. castaneum , and its role in immune defence in response to bacterial challenge was also investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Identi cation of parasite/pathogen invasion in the host is the initial step in the initiation of immune responses, and this process relies on biosensor proteins called pattern recognition receptors (PRRs), which can detect and bind to certain pathogen-associated molecular patterns (PAMPs) on the surface of invading microbes or foreign bodies [52,53]. PGRPs are important members of insect PRRs and play an important role in innate immunity [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…On the structural level, the lectin protein family is tightly related to cold tolerance ( Moulessehoul et al, 1992 ; Gronwald et al, 1998 ). Interestingly, the function of lectin proteins relies on alpha1,3-galactosyltransferase ( Khraltsova et al, 2000 ), cytoskeleton ( Timofeeva et al, 2000 ), and especially rely on the lectin type ( Meng et al, 2017 ; Hung et al, 2018 ). In this study, three C-type lectin proteins were differentially expressed under the different temperature treatments (Figure 5 ), suggesting that each individual lectin played a specific role in cold tolerance in this organism.…”
Section: Discussionmentioning
confidence: 99%